Chapter 1. Remarks on the opening of the historic place names of Franz Josef Land workshop, Oslo, Norway, 12-13 May 2015 - Barr, Susan (Septentrio Conference Series, 2015)
Remarks at the opening of a workshop, sponsored by the U.S. National Science Foundation, and held in Oslo, Norway, from 12-13 May 2015, to discuss the historic place names of the High Arctic archipelago of Franz Josef Land. The visiting students from Penn State University, none of whom had ever before been to Europe, were anxious to hear how Dr. Barr, a native of the United Kingdom, had come to Norway and made a life for herself in a different country with a different language, as a female in a then-largely male universe of polar research, and, in a nation of hunters, as a vegetarian.